Chinese Clinical Trial Registry 13-year data collection and analysis: geographic distribution, financial support, research phase, duration, and disease categories - Fan, Ruitai; Zheng, Yufei; Zhou, Runze; Beeraka, Narasimha M.; Sukocheva, Olga A.; Zhao, Ruiwen; Li, Shijie; Zhao, Xiang; Liu, Chunying; He, Song; Mahesh, P. A.; Gurupadayya, B. M.; et al. (Frontiers in Medicine, 2023)
What are the current characteristics of clinical trials registered on the Chinese Clinical Trial Registry (ChiCTR) platform in the last 13 years?In this descriptive research, clinical trials pertinent to neoplastic diseases occupied the largest portion of registrations. Publicly funded trials accounted for a comparatively higher number than the trials funded by other sources. Research on oncological and cardiovascular diseases receives the highest share of national public funding for medical research when compared to other types of disease research.This study provides significant insights and background for the development of regulations that promote greater transparency and accuracy in clinical trial registrations and research distribution.